Parent Report and Actigraphically Defined Sleep in Children with and without Developmental Coordination Disorder; Links with Fatigue and Sleepiness - Wiggs, Luci; Sparrowhawk, Masako; Barnett, Anna L. (Frontiers in Pediatrics, 2016)
Background: Impaired sleep is associated with negative effects on quality of life and daytime functioning. Higher rates of sleep disturbance are reported in children with various developmental disorders. However, little is known about sleep in children with Developmental Coordination Disorder (DCD), a condition characterized by everyday movement difficulties. Previously, in a preliminary study, we found higher rates of parent-reported sleep disturbance in children with DCD compared to controls. Aims: To examine sleep in DCD using objective measures and to examine links with daytime fatigue and sleepiness. Methods: Two groups (primary and secondary school-aged) of 15 children with DCD, plus matched controls, participated. Parent reported child sleep was assessed using the Children’s Sleep Habits Questionnaire and actigraphy provided an objective measure of sleep-wake patterns over one week (including weekdays and weekend). Pediatric Restless Legs Syndrome (RLS) Semi-Structured Diagnostic Interview was conducted with each child and parent to capture symptoms of RLS. Aspects of self-rated child functioning were assessed with questionnaires (Pre-sleep Arousal Scale, Pediatric Daytime Sleepiness Scale, PedsQL Multidimensional Fatigue Scale) and mothers’ reported thoughts about child sleep with the Maternal Cognitions about Infant Sleep Questionnaire. Results: The DCD groups had greater parent-reported sleep disturbance. Actigraphy results suggested that for secondary aged children with DCD their sleep quality was impaired and there were differences in the timing of sleep compared to controls (including some differences in the variation between weekday and weekend sleep times). The actigraphy of the primary age group with DCD was unremarkable compared to controls. No child in the study met the criteria for RLS. Exploratory analyses suggested that daytime fatigue, aspects of pre-sleep arousal and daytime sleepiness were reported as greater in the DCD groups and were particularly related to objective sleep parameters in the DCD groups. Maternal thoughts about sleep did not differ between the DCD and control groups. Conclusions: The nature and underlying cause of sleep disturbance and how it might be linked with aspects of daytime functioning in adolescents with DCD requires further research. Meanwhile, clinical awareness of the risk of atypical sleep patterns/sleep problems in DCD is important to ensure early identification and